Influence of Different Levels of Ground Oak (Quercus Aegilops) Acorns on Growth Performance and Some Carcass Characteristics of Awassi Lambs - Hidayet, Hoger M.; Mustafa, Kamal N. (Science Journal of University of Zakho, 2020)
This study was aimed to investigate the effect of feeding different levels of oak acorns on growth and some carcass characteristics of Awassi lambs. Twenty lambs were blocked into four groups (5 lambs/ group) according to live body weight and fed on one of the experimental diets (0, 5, 10 and 15% oak acorns). The results showed no effect of dietary treatments on live body weight throughout the period of study, also there were no effects of treatments on carcass traits except for rib-eye muscle area which was largest in the group fed on 5% acorns. It could be concluded that feeding Awassi lambs on ground oak acorns has no adverse effects on growth performance and health condition.